Randomized Response Techniques: Its Development in Six Decades - Raghunath Arnab (Journal of the Indian Society of Agricultural Statistics, 2026)
Randomized response techniques (RR) are used to collect data relating to sensitive, personal, and /or stigmatizing characteristics. The direct method (DR) of interview cannot be applied in such situations because the respondents generally do not reveal the true information due to the social stigma and /or fear. So, the respondents often provide socially approved or untrue responses. As a result, DR suffers from inaccurate data and a high rate of nonresponse. To overcome such difficulties, Warner (1965) introduced an ingenious method of data collection, known as the randomized response (RR) technique, where respondents need not provide the true response but only to provide the outcome of a random experiment. Respondents’ privacy is maintained, as the interviewer will not identify whether the submitted response is true or masked. A chronological development of the RR techniques for the last six decades is provided, starting with the pioneering RR model provided by Warner. Detailed developments of the RR models for the qualitative and quantitative characteristics are provided along with the applications for the complex survey designs. Methods of estimation of the population characteristics from the multiple randomized response techniques are presented. The methods of estimations of the proportions of overlaps of multiple characteristics are presented. The optional randomized response techniques (ORT) are also discussed. Finally, some of the nonrandomized response techniques (NRR) and the measures of privacy protection are presented.